Features of a shock wave in CdTe by pulsed laser irradiation - Dauletmuratov, B.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Analyzed on the example of CdTe are formation and propagation of shock waves during pulsed laser irradiation of a solid surface. It is shown that before the appearance of a shock wave in a solid, a gradual increase in pressure gradient leads to formation of dislocations, density of which increases with depth. The dislocation density is maximum at the place of shock wave formation.